2007
DOI: 10.1021/jp071968l
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Interaction with a Ceria−Zirconia Supported Gold Catalyst. Influence of CO Co-adsorption and Pretreatment Conditions

Abstract: This work reports on the hydrogen interaction with a 3 wt % Au/Ce 0.62 Zr 0.38 O 2 (Au/CZ) catalyst prepared by deposition-precipitation. As deduced from X-ray powder diffraction, electron microscopy (scanning transmission electron microscopy-high-angle angular dark field and high-resolution electron microscopy), and CO volumetric/Fourier transform IR (FTIR) adsorption studies, the investigated catalyst shows a good metal dispersion. By combining FTIR spectroscopy and volumetric chemisorption studies, it is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 71 publications
4
78
0
Order By: Relevance
“…As revealed by the FTIR studies, 33 at 298 K under P(CO) ranging from 0 to 300 Torr, three major components contribute to the CO adsorption on Au/CZ catalysts. The first one due to CO adsorbed on Au(0) nanoparticles is characterized by a¯-CO stretching band typically occurring at about 2110 cm ¹1 .…”
Section: ç 2 Quantitative Estimate Of Metal Andmentioning
confidence: 99%
See 2 more Smart Citations
“…As revealed by the FTIR studies, 33 at 298 K under P(CO) ranging from 0 to 300 Torr, three major components contribute to the CO adsorption on Au/CZ catalysts. The first one due to CO adsorbed on Au(0) nanoparticles is characterized by a¯-CO stretching band typically occurring at about 2110 cm ¹1 .…”
Section: ç 2 Quantitative Estimate Of Metal Andmentioning
confidence: 99%
“…33 Details of the preparation and activation routines are given in ref 33. The comparison of the spectra recorded at 298 K under P(CO) = 100 Torr and after 30 min evacuation at 298 K showed that the weak adsorbed forms, i.e., those corresponding to COAu and CO interacting with the surface Ce 4+ and Zr…”
Section: ç 2 Quantitative Estimate Of Metal Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ceria supported gold systems attracted a lot of attention as the catalysts for low-temperature water gas-shift, carbon monoxide oxidation and PROX reactions. In the last 5 years several tens of relevant papers have been published, most of which being quoted in the papers [7,8]. However, pure ceria is relatively resistant to reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Such unique properties of ceria-zirconia systems seem to make them ideally suited for an application as supports to gold catalysts. Surprisingly, only a few papers concerning Au/Ce x Zr 1-x O 2 catalysts [7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], tested mainly in the water-gas shift reaction [9][10][11][12][13][14][15][16] and low-temperature CO oxidation [10,[17][18][19][20][21][22][23] have been published so far. In this paper the most important achievements and conclusions coming from these contributions have been reviewed.…”
Section: Introductionmentioning
confidence: 99%